2016
DOI: 10.1016/j.jtcvs.2015.09.077
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group box-1 protein induces osteogenic phenotype changes in aortic valve interstitial cells

Abstract: The HMGB1 protein may promote osteoblastic differentiation and calcification of VICs, through the TLR4-JNK-NF-κB signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…Passmore et al [26] demonstrated that osteopontin altered endothelial and VIC behavior in calcific AV stenosis through HMGB1 regulation. Our previous work also suggested that HMGB1 induced high production of pro-inflammatory cytokines and promoted the osteoblastic differentiation and calcification of VICs [7]. In this study, we further supported the role of HMGB1 in CAVD by demonstrating that HMGB1 could also induce myofibroblastic transition of VICs.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Passmore et al [26] demonstrated that osteopontin altered endothelial and VIC behavior in calcific AV stenosis through HMGB1 regulation. Our previous work also suggested that HMGB1 induced high production of pro-inflammatory cytokines and promoted the osteoblastic differentiation and calcification of VICs [7]. In this study, we further supported the role of HMGB1 in CAVD by demonstrating that HMGB1 could also induce myofibroblastic transition of VICs.…”
Section: Discussionsupporting
confidence: 84%
“…We found that the expression of IL-18 and HMGB1 was markedly increased in calcific AVs compared to normal ones (fig. 1a, b, d) [7]. Transition from VICs to myofibroblasts is a critical step in valvular pathology [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was demonstrated that HMGB1 can trigger the differentiation of mesenchymal stem cells into osteoblasts, which may provide a theoretical basis for improving clinical treatments for fractures [63, 64]. Wang et al observed that HMGB1 promotes osteoblastic differentiation and calcification of aortic valve interstitial cells (VICs) through TLR4-JNK-NF-κB signaling [65]. …”
Section: Possible Mechanisms By Which Hmgb1 Promotes Cardiovascular Cmentioning
confidence: 99%
“…Valves extracted during operation for aortic dissection. 35,37 These valves are perhaps closest to normal as long as the underlying predisposing cause of dissection is presumed not to affect the aortic valve. One problem is to obtain the valves: these are acute patients admitted at any time of the day or night.…”
mentioning
confidence: 99%